The activation states of LFA-1 (αLβ2) and related integrins - Cheng, Ming (2010)
Cell adhesion molecules, which are both receptors and ligands for receptors, are typically transmembrane proteins. They are composed of three domains: an intracellular domain that interacts with the cytoskeleton, a transmembrane domain and an extracellular domain that interacts either with other cell adhesion molecules on another cell or the component of the extracellular matrix (ECM) (Joseph-Silverstein and Silverstein, 1998). Their functions include adhesion, recognition and communication between cells and between cells and components of the extracellular matrix.